In situ elevated temperature testing of fly ash based geopolymer composites - Vickers, L.; Pan, Z.; Tao, Z.; Van Riessen, Arie (mdpi, 2016)
In situ elevated temperature investigations using fly ash based geopolymers filled with alumina aggregate were undertaken. Compressive strength and short term creep tests were carried out to determine the onset temperature of viscous flow. Fire testing using the standard cellulose curve was performed. Applying a load to the specimen as the temperature increased reduced the temperature at which viscous flow occurred (compared to test methods with no applied stress). Compressive strength increased at the elevated temperature and is attributed to viscous flow and sintering forming a more compact microstructure. The addition of alumina aggregate and reduction of water content reduced the thermal conductivity. This led to the earlier onset and shorter dehydration plateau duration times. However, crack formation was reduced and is attributed to smaller thermal gradients across the fire test specimen.